1993
DOI: 10.1021/bi00085a028
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the carboxy terminus of HIV-1 Rev affects multimerization on the Rev responsive element

Abstract: Perturbations within the transactivation and carboxy-terminal domains of HIV-1 Rev were examined for effects on Rev responsive element (RRE) binding activities in vitro and biological activity in vivo. Binding affinities, specificities, and multimerization of the transactivation mutants M10 and Rev/Rex M10-16 on the RRE were equivalent to wild-type Rev. Substitution of the Rex transactivation domain within Rev resulted in the incorporation of an internal methionine residue which, when cleaved with CNBr and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
6
26
1
2
Order By: Relevance
“…Although the kinetics presented here cannot settle this dispute, the fact that the minimal high affinity binding site (RRE/SLIIB) bound Rev at a 1:1 ratio and the slightly larger RRE/HH yields a 2:1 protein:RNA ratio suggested that the initial binding to RRE must involve a Rev monomer, followed by multimerization in situ, in agreement with previous reports (10,58,81,82). It has also been suggested that a critical threshold level of Rev on RRE is required for trans-activation (59,61,79,80) and also that the RRE acts as a molecular rheostat (59) regulating the sequential addition of Rev monomers to achieve the critical threshold.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the kinetics presented here cannot settle this dispute, the fact that the minimal high affinity binding site (RRE/SLIIB) bound Rev at a 1:1 ratio and the slightly larger RRE/HH yields a 2:1 protein:RNA ratio suggested that the initial binding to RRE must involve a Rev monomer, followed by multimerization in situ, in agreement with previous reports (10,58,81,82). It has also been suggested that a critical threshold level of Rev on RRE is required for trans-activation (59,61,79,80) and also that the RRE acts as a molecular rheostat (59) regulating the sequential addition of Rev monomers to achieve the critical threshold.…”
Section: Discussionsupporting
confidence: 91%
“…Because RRE/SLIIB can only bind one molecule of Rev, cooperative binding was not an issue. Furthermore, because Rev bound with high affinity to RRE/SLIIB, this showed that high affinity binding is possible in the absence of multimerization, in agreement with the suggestion of Daly et al (81,82).…”
Section: Discussionsupporting
confidence: 90%
“…As discussed earlier, mutants of this type exhibit RRE binding and nucleolar localization characteristics that are indistinguishable from those of the wild-type protein (Fig. 2i,j;Malim et al 1989a;Olsen et al 1990;Zapp et al 1991;Daly et al 1993). Importantly, and in striking contrast to Rev, the M10 protein failed to accumulate in the cytoplasms of transfected HeLa cells following treatment with 5 p.g/ml of actinomycin D (Fig.…”
Section: R E S U L T Smentioning
confidence: 55%
“…The second essential domain contains three closely spaced leucine residues and is positioned toward the carboxyl terminus (Venkatesh and Chinnadurai 1990;. The mutation of any of these leucines generates nonfunctional proteins (Malim et al 1989a;Hope et al 1990b;Mermer et al 1990;Olsen et al 1990;Venkatesh and Chinnadurai 1990) whose predominant accumulation in the nucleoli and ability to bind to the RRE are both indistinguishable from wild-type Rev (Malim et al 1989a;Olsen et al 1990;Zapp et al 1991;Tiley et al 1992;Daly et al 1993). It has therefore been proposed that the defect in Rev mutants with this phenotype lies in their inability to interact with the nuclear factors, presumably proteins, required for the transport of unspliced HIV-1 mRNA to the cytoplasm {Malim et al 1991).…”
Section: Receivedmentioning
confidence: 99%
“…Oligomerization of Rev requires the Rev multimerization domain that has also been shown to be necessary for Rev function (12,34,39,42,54). Additionally, the molecular details of the interaction of the Rev monomer and its primary binding site have been well characterized through the use of an isolated Rev peptide containing only the arginine-rich binding motif (ARM) and the stem IIB RNA hairpin (3,4,48,49).…”
Section: Cells Infected With Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%